2017
DOI: 10.1128/aem.00028-17
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Comparison of Human Wastewater-Associated Molecular Markers in Relation to Fecal Indicator Bacteria and Enteric Viruses in Recreational Beach Waters

Abstract: Detection of human wastewater contamination in recreational waters is of critical importance to regulators due to the risks posed to public health. To identify such risks, human wastewater-associated microbial source tracking (MST) markers have been developed. At present, however, a greater understanding of the suitability of these markers for the detection of diluted human wastewater in environmental waters is necessary to predict risk. Here, we compared the process limit of detection (PLOD) and process limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 41 publications
3
64
0
Order By: Relevance
“…34 Beach water samples taken from southeast Queensland, Australia, were tested for PMMoV as an MST organism for fecal pollution of coastal environments. 35 Results from this study yielded only 33.3% (4/12) water samples positive for PMMoV. Concentrations recovered for these samples ranged from 3.6 × 10 4 to 8.6 × 10 4 GC/L ( Table 2).…”
Section: Marine Environmentmentioning
confidence: 75%
See 3 more Smart Citations
“…34 Beach water samples taken from southeast Queensland, Australia, were tested for PMMoV as an MST organism for fecal pollution of coastal environments. 35 Results from this study yielded only 33.3% (4/12) water samples positive for PMMoV. Concentrations recovered for these samples ranged from 3.6 × 10 4 to 8.6 × 10 4 GC/L ( Table 2).…”
Section: Marine Environmentmentioning
confidence: 75%
“…1). 28,[31][32][33][34][35] These studies reported that PMMoV was detected in almost all untreated wastewater samples with concentrations greater than 10 5 genome copies (GC)/L ( Table 2). One recent study carried out in Costa Rica documented that the specificity of PMMoV qPCR signal was 100% for domestic wastewater, as compared to 94% specificity of a human-specific (HF183) Bacteroides marker.…”
Section: Wastewater and Reclamation Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…somatic and Fþ coliphages), genotypes of FRNA phages and plant virus (i.e. PMMoV) have recently been proposed to allow for better prediction of human pathogens (Hughes et al, 2017;McQuaig et al 2009McQuaig et al , 2012Vergara et al, 2015;Yampara-Iquise et al, 2008). As a result, a number of recent studies have focused on correlations between the alternative indicators and pathogens (Harwood et al, 2014;Jofre et al, 2016).…”
Section: Correlations Between Indicators Pathogens and Environmentalmentioning
confidence: 99%